Skateboarding Between Subculture and the Olympics: A Youth Culture under Pressure from Commercialization and Sportification - Kilberth, Veith; Schwier, Jürgen (transcript, 2019)
The inclusion of skateboarding as an official discipline in the 2020 Olympic Games marks the pinnacle of a decades-long process of commercialization and sportification. Is the tightly-knit subculture in danger of losing its very identity?This anthology creates an analytical framework for understanding the fundamental conflict between skateboarding's core ethos and the tenets of institutionalized sports. Eleven acclaimed international authors from the fields of architecture, philosophy, sociology, sports sciences and gender studies provide a unique perspective on the manifold manifestations of skateboarding previously ignored by academic discourse.